Women, Illegal Online Loans, and the Myth of Irrationality: Debunking Structural Claims on Women's Financial Vulnerability through Feminist Vulnerability Theory - Hastanti Widy Nugroho (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
The rapid expansion of digital financial services has increased access to credit but has also intensified the risks associated with illegal online lending, particularly among women in Indonesia. This study aims to critically examine the dominant narrative that attributes women’s vulnerability to irrationality and low financial literacy by analyzing the paradox between financial literacy levels and victimization rates. Using a qualitative design grounded in feminist philosophical analysis, this study integrates critical secondary data analysis and a systematic literature review from national and international sources published between 2021 and 2026. The findings reveal a significant empirical contradiction in which women demonstrate comparable or higher financial literacy than men, yet consistently constitute the majority of victims of illegal online loans. This indicates that vulnerability is not primarily driven by individual factors but by structural conditions, including limited access to formal credit, wage inequality, unpaid care burdens, and the presence of predatory lending systems characterized by excessive interest rates and exploitative practices. Furthermore, weak regulatory frameworks and institutional failures exacerbate these vulnerabilities. Drawing on Feminist Vulnerability Theory and feminist political economy, this study concludes that women’s financial decisions should be understood as rational responses to structurally constrained conditions rather than as indicators of individual deficiency. The study contributes to a paradigm shift from individualistic explanations toward structural analysis and highlights the need for comprehensive policy reforms, including gender-responsive financial systems, stronger consumer protection, and recognition of unpaid care work in economic structures.